1999
DOI: 10.1046/j.1365-2036.1999.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the pharmacokinetics of rabeprazole in health and disease

Abstract: Rabeprazole, a newly developed proton pump inhibitor, has been shown to be effective for the treatment of gastric and duodenal ulcers and for gastro-oesophageal reflux disease. It is a rapid and potent inhibitor of gastric H+,K(+)-ATPase, the gastric acid (proton) pump. The maximum plasma concentration (Cmax) and the area under the plasma concentration time curve (AUC) are linearly related to dose, while the time to maximum plasma concentration (tmax) and elimination half-life (t1/2) are dose-independent. Rabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
3
22
1
Order By: Relevance
“…Generally, rabeprazole or lansoprazole are coadministered with tacrolimus, an immunosuppressive agent, in renal transplant recipients suffering from gastric ulcer disease (Homma et al 2002). These drugs are extensively metabolized in the liver, since the parent drug is not detected in the urine (Tateno and Nakamura 1991;Swan et al 1999). Similar to the results of studies in healthy subjects (Kim et al 2002;Miura et al 2004b), the metabolism of lansoprazole in renal transplant recipients is stereoselective, and the metabolism rate of the (R)-enantiomer is lower and less variable than that of the (S)-enantiomer, resulting in higher plasma concentrations of the (R)-enantiomer following administration of the same dose.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, rabeprazole or lansoprazole are coadministered with tacrolimus, an immunosuppressive agent, in renal transplant recipients suffering from gastric ulcer disease (Homma et al 2002). These drugs are extensively metabolized in the liver, since the parent drug is not detected in the urine (Tateno and Nakamura 1991;Swan et al 1999). Similar to the results of studies in healthy subjects (Kim et al 2002;Miura et al 2004b), the metabolism of lansoprazole in renal transplant recipients is stereoselective, and the metabolism rate of the (R)-enantiomer is lower and less variable than that of the (S)-enantiomer, resulting in higher plasma concentrations of the (R)-enantiomer following administration of the same dose.…”
Section: Resultsmentioning
confidence: 99%
“…Following oral ingestion, it is relatively rapidly absorbed and the peak plasma concentration reaches 2.8 -5.1 mg/ml [8] . Overall bioavailability is 52% with a standard dose of 20 mg. Rabeprazole does not have a saturable first-pass metabolism and can be absorbed continually at higher doses.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…After repeated ingestion of rabeprazole, no significant accumulation occurs because the elimination half-life is 1 h after single and 1.5 h after several administrations. Of a 20 mg dose, 90% is excreted in the urine and 10% in the faeces [8][9][10] .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The clearance of drugs that undergo phase II metabolism [e.g., mizolastine (Lebrun-Vignes et al, 2001)] is unchanged in old age, whereas drugs that undergo phase I metabolism [e.g., ropinirole (Kaye and Nicholls, 2000), citalopram (Gutierrez and Abramowitz, 2000), rabeprazole (Swan et al, 1999), argatroban (Swan and Hursting, 2000)] have reduced clearance in older people. On the other hand, a review of pharmacokinetics found that aging in volunteers and subjects with rheumatoid arthritis was not associated with any significant change in cyclosporin pharmacokinetics; although, clearance was lower in older renal transplant recipients (Kovarik and Koelle, 1999).…”
Section: In Vitro Studies Of Aging and Hepatic Drug-metabolizing Enzymentioning
confidence: 99%